2019
DOI: 10.1186/s12967-019-1996-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo model of human post-traumatic heterotopic ossification demonstrates early fibroproliferative signature

Abstract: Background The relationship between the tissue injury healing response and development of heterotopic ossification (HO) is poorly understood. Here we compare a rat blast model and human traumatized muscle from a blast injury to study the early signatures of osteogenesis and fibrosis during the formation of HO. Methods Rat and human tissues were characterized using histology, scanning electron microscopy, immunohistochemistry, as well as gene and protein expression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, severe consequences of calcium administration have also been reported, such as cardiac cellular apoptosis and the precipitation of calcium salts. 31 Achieving the right balance requires further study to avoid complications of undertreatment or overtreatment of hypocalcemia in trauma.…”
Section: Discussionmentioning
confidence: 99%
“…However, severe consequences of calcium administration have also been reported, such as cardiac cellular apoptosis and the precipitation of calcium salts. 31 Achieving the right balance requires further study to avoid complications of undertreatment or overtreatment of hypocalcemia in trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers from Pellegrini's lab established the HO rat model following blast Am procedure, and found that HO demonstrated early fibroproliferative signature. 17,18 In addition, the study from Forsberg and Potter's lab confirmed that the serum from HO patients could activate mitogen activated protein kinase signaling in adipose stem cells. 19 The authors from Levi and Davis's Lab found that BMP signaling made great contribution to osteogenic differentiation as well as ectopic bone formation and blocking BMP signaling may be an effective prophylactic strategy for HO following blast-related lower extremity trauma.…”
Section: Discussionmentioning
confidence: 90%
“…The NGS panel contained 21 ectopic mineralization-associated genes (ABCC6, ADIPOQ, AHSG, ANKH, APOE, ATF4, CASR, ENPP1, FAM20A, FGF23, GALNT3, GGCX, KL, MGP, NT5E, SAMD9, SLC20A2, SLC29A1, SPP1, TRIM24, and TNFRSF11B) 8 and 8 genes (A2AP, ALPL, ENTPD1, PAI-1, PLAT, PLAU, PLAUR, and PLG) involved in the fibrinolysis pathway and regulation of ectopic mineralization in soft tissue after injury. [9][10][11][12] We performed variant detection and bioinformatic analyses according to previously published approaches. 13,14 Final prioritization of variants employs a 2-tiered procedure following the latest American College of Medical Genetics and Genomics/Association for Molecular Pathology (ACMG/AMP) 15 and Sherloc guidelines.…”
Section: Targeted Multigene Ngs Sequencing and Bioinformaticsmentioning
confidence: 99%